Three Essays In Industrial Organization, Law And Finance - Shahriari, Hesam (My University, 2016)
This thesis explores three important topics spanning international asset pricing, empirical capital structure, U.S. politics, and corporate law: relationship-specific investment (RSI), contracting environment and financial performance; RSI, contracting environment and the choice of capital structure; and political value and SEC enforcement actions. Firms that engage in long-term bilateral relationships with their buyers or suppliers are usually required to make relationship-specific investments. We examine how the values of these long-term specific investments are affected by the quality of governmental contract enforcement. We find that firms in relationship-specific industries have higher valuations, measured by Tobin’s Q, when their countries of origin are able to strongly enforce contractual agreements. Our finding is robust to a variety of empirical specifications and regression methods. We also show that as legal quality improves, firms with relationship-specific investments exhibit lower operating performance, presumably due to risk or in order to motivate further investments from their stakeholders. Further analysis of the cross-section of stock returns supports a risk-based explanation. Firms in long-term bilateral relationships with their customers or suppliers are required to make relationship-specific investments in the form of physical equipment, human resources, specific production sites, or brand names. These dedicated assets are usually tied to a particular use or relationship and cannot be redeployed if the firm is liquidated. In the absence of legal enforcement, firms are required to limit their use of debt financing and, consequently, signal a reduced default risk to encourage investment by their contracting parties. Using a sample of 143,278 firm-year observations, and measures of industry-level relationship-specificity and the quality of legal enforcement across 57 countries, we find strong evidence that good quality contract enforcement mitigates the negative association between relationship-specificity and debt financing. The Securities and Exchange Commission (SEC) plays a central role in investigating potential violations of securities laws and initiating enforcement actions in the United States. We examine the association between political culture and political connections and the penalties imposed at the end of SEC enforcement actions. Our analysis is based on two key ideas. First, the political culture of a firm indicates its ethical boundaries and explains the propensity of misconduct across different domains, such as securities laws. Second, political connections signal a firm’s willingness to challenge SEC’s enforcement decisions. We find that the individual defendants associated with Republican firms are less likely to receive a bar or suspension penalty. This finding supports the notion that Republican managers are less likely to commit securities fraud since the Republican ideology stresses market discipline. Moreover, in line with prior research, our results show that political connections and firm size, as a proxy for bargaining power, also reduce penalties imposed in SEC enforcement actions.
Keywords: Capital structure; Law and finance; Industrial organization; International capital markets